2010
DOI: 10.1177/0017896910364837
|View full text |Cite
|
Sign up to set email alerts
|

A tale of two localities

Abstract: Objective:To determine the availability and affordability of a healthy food basket and to model how those on low-incomes might manage. Design and methodology: After determining access and availability of key items from shops in two localities, called Deepdale and Ingol, a healthy food basket was developed. From this a week's healthy menu was devised for a mother and two children, then availability of the ingredients was checked using data collected from the shops and costed. The baskets represented the cultura… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(3 citation statements)
references
References 9 publications
0
3
0
Order By: Relevance
“…In another recent study undertaken in the UK (Lloyd et al 2011), there was found to be a huge discrepancy in the cost of buying healthy food to feed a family on a low income for a week. It was concluded that in some areas it could well work out cheaper to buy the high-fat unhealthy fast food in local outlets, particularly once you have taken into account the cooking of the food.…”
Section: Institute Of Health Promotion and Educationmentioning
confidence: 97%
“…In another recent study undertaken in the UK (Lloyd et al 2011), there was found to be a huge discrepancy in the cost of buying healthy food to feed a family on a low income for a week. It was concluded that in some areas it could well work out cheaper to buy the high-fat unhealthy fast food in local outlets, particularly once you have taken into account the cooking of the food.…”
Section: Institute Of Health Promotion and Educationmentioning
confidence: 97%
“…Community organisation providers also talked about households in their communities that had a food budget of just fifteen to twenty pounds a week. Food-using charities revealed, that while these families may not be at crisis point, and therefore accessing emergency food, their diets still are not sufficient to meet the requirements of the national nutritional guidelines, which in the UK is known as the Eatwell plate [45]. Some forgo eating meals.…”
Section: How Poverty and Food Insecurity Intersectmentioning
confidence: 99%
“…Food affordability impacts not only the wider economy through the impacts on spending patterns, but also on health by affecting the ability to purchase healthy and nutritious food [20,21]. While some household expenses are fixed (e.g., rent or utility expenses), the food budget is changeable and can be cut back if needed with nutrition consequences [22]. If one household expense increases (e.g., an increase in rent) then this will impact on that household’s food affordability leading to additional stress on the food budget; i.e., food stress.…”
Section: Introductionmentioning
confidence: 99%